Strategy to Increase Students Interest in Reading through School Literacy Programs in The Era of Digital Transformation in Junior High School - Wardah, Ariza Ulatul; Huda, Miftakhul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research aims to formulate strategies implemented by schools to increase students' interest in reading through school literacy programs in the era of digital transformation. Methodology: The method used in this research is descriptive qualitative. This research was carried out at SMP Negeri 1 Jetis Ponorogo using data collection techniques through interviews, observation and documentation. Sources of research data came from the principal, library director, teachers and students. The data analysis technique uses data triangulation, namely by collecting data, reduplicating data, presenting data, and drawing conclusions. Results: The strategy implemented by the school in an effort to increase students interest in reading is good and proven to be effective, as it aligns with the success indicators mutually agreed upon by the school as its goal in increasing students interest in reading in the era of digital transformation. The strategy implemented is through (a) the Sabu Saku (One Month One Book) movement with outputs in the form of books and short films based on print and digital media, (b) literacy corners as the school's effort to promote interest in reading in strategic corners of the school, (c) the existence of a cultural and arts studio, (d) a digital library, and (e) the selection of literacy ambassadors as one of the supporters and pioneers of fostering love and appreciation for books. Applications/Originality/Value: The data validity technique uses data validity tests in the form of credibility, transferability, dependability, and confirmability tests which are of course adapted to the conditions in the field.